Perceived implementation of patient safety compliance among nursing supervisors in military hospitals: a descriptive qualitative study - Setiawati, Deni; Setyowati , Setyowati; Hariyati, Rr. Tutik Sri; Mediawati, Ati Surya; Hidayanto, Achmad Nizar; Putro, Prasetyo Adi Wibowo (Jurnal Ners, 2024)
Introduction: Patient safety incidents remain high in Indonesia and are a significant responsibility of nursing supervisors working in military hospitals. The purpose of this study was to explore the understanding and perception of nursing supervisors in implementing patient safety compliance in military hospitals. Methods: A descriptive qualitative approach was conducted with nursing supervisors at a military hospital through in-depth interviews. A total of 25 nursing supervisors from military hospitals participated in the interviews. The content analysis was employed to analyze the interview data. Results: Five themes were identified in this study: patient safety as our responsibility, implementation in practice, support in safety initiatives, barriers to safety goals, and tech-driven safety efficiency. Conclusions: The findings underscore that an in-depth understanding by nursing supervisors is critical to fostering appropriate behavior, particularly in achieving patient safety goals. Nursing supervisors articulated expectations for improvements in healthcare quality. As healthcare professionals, nursing supervisors must grasp the significance of a patient safety approach and be adept at executing it to enhance the quality of care, which will, in turn, lead to better healthcare outcomes.